Cuticular wax in wheat: biosynthesis, genetics, and the stress response - Tian, Ruiyang; Liu, Wendi; Wang, Yuhai; Wang, Wenqiang (Frontiers in Plant Science, 2024)
All terrestrial plants possess a hydrophobic cuticle in the outermost layer of their aerial organs that is composed of cutin and wax. The cuticle serves as the first barrier between the plant and the surrounding environment and plays a key role in the resistance of plants to abiotic and biotic stressors. Additionally, they are closely associated with plant growth and development. Cuticular wax has attracted considerable attention as the main mediator of cuticular functions. In this review, we summarize the advances in the research investigating wheat cuticular wax, focusing on three aspects that include biosynthesis, genetics, and stress responses. Additionally, we discuss the applications of cuticular wax in wheat breeding.